Representation of Domestic Violence Victims in the Lyrics of 'Ibu' by Pangalo! : Sara Mill's Critical Discourse Analysis - Aidil Fitrian; Sihaloho, Firmauli (Indonesian Journal of Linguistics, 2000)
Domestic violence is still a complex social issue in Indonesia, where women are often positioned as victims in a patriarchal culture that normalizes violence as part of the marriage relationship. This phenomenon is interesting to study through the lyrics of the song ‘Ibu’ by Pangalo!, which depicts a critical reflection on gender construction and power relations in popular culture. This research aims to explore how domestic violence is represented in the lyrics of the song ‘Ibu’ by Pangalo! through Sara Mills’ Critical Discourse Analysis. The method used was qualitative with a linguistic approach (critical discourse analysis) based on Sara Mills’ model. Findings show that the lyrics of the song ‘Ibu’ strongly reflect patriarchal ideology, depicting mothers as passive victims who endure physical and emotional violence while justifying their suffering due to cultural and religious dogma. However, Pangalo! also shows resistance in his lyrics, challenging the normalization of domestic violence and fighting for gender equality. This study demonstrates that popular music can serve as a medium of social critique by exposing the normalization of gender-based violence. The results contribute to gender and communication studies by showing how song lyrics shape empathy toward victims and raise awareness of equality, making this research relevant for future cultural discourse analysis.